2012
DOI: 10.1038/labinvest.2012.80
|View full text |Cite
|
Sign up to set email alerts
|

CCL2 disrupts the adherens junction: implications for neuroinflammation

Abstract: Alterations to blood-brain barrier (BBB) adhesion molecules and junctional integrity during neuroinflammation can promote central nervous system (CNS) pathology. The chemokine CCL2 is elevated during CNS inflammation and is associated with endothelial dysfunction. The effects of CCL2 on endothelial adherens junctions (AJ) have not been defined. We demonstrate that CCL2 transiently induces Src-dependent disruption of human brain microvascular endothelial AJ. β-catenin is phosphorylated and traffics from the AJ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 111 publications
0
71
0
Order By: Relevance
“…Chemokines also have an effect on BBB disruption, as demonstrated for MCP-1 (CCL2) during HIV-1 infection, where MCP-1 disrupts adherens junctions and transiently opens the endothelial cell barrier (53). Chemokines also affect BBB integrity by enhancing migration of immune cells to the infected brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…Chemokines also have an effect on BBB disruption, as demonstrated for MCP-1 (CCL2) during HIV-1 infection, where MCP-1 disrupts adherens junctions and transiently opens the endothelial cell barrier (53). Chemokines also affect BBB integrity by enhancing migration of immune cells to the infected brain areas.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that CCL2 expression is induced by increased levels of b-amyloid, and this can in turn disrupt the blood-brain barrier and facilitate recruitment of leukocytes into the CNS. 43 In mouse models of Alzheimer's disease, monocytes have been showed to migrate from the bone marrow and infiltrate into brain in a CCR2-dependent manner, and then differentiate into microglia or macrophages. There is growing evidence that CCR2 þ cells may play protective rather than detrimental roles in Alzheimer's disease.…”
Section: Evidence For a Role Of Ccr2 In Central Nervous System Diseasesmentioning
confidence: 99%
“…Thus, CCL2 increases the ability of endothelium to recruit leukocytes into CNS and disrupt the BBB. CCL2 increase in CNS and cerebrospinal fluid has been promoted as a marker of damage to BBB in patients with a neuroinflammatory background [133].…”
Section: Advances In Diagnosis Of Cns Involvement In Leukemiamentioning
confidence: 99%